Government's record on health services - Labour Party (Great Britain). Advisory Committee on Public Health
1927-09 1927 1920s 11 pages - 9 - to apply. In the past workshops have been exempt from these provisions, unless women or young persons were employed. The responsibility for securing these provisions was to be transferred to the Factory Department of the Home Office, whereas previously the control of the sanitary conditions of "workshops" had been the charge of the local authority. The Bill insisted on the proper lighting, heating, cleaning and sanitary accommodation of all factories. Medical supervision was to be given to all factories, such as boot and shoe and printing works, where there is a specially high rate of tuberculosis and other diseases. The provision of drinking water, washing facilities, first aid, seating, cloakroom and means for clothes drying, and protective clothing in certain trades, were to be compulsory. An important clause proposed to regulate the carrying of heavy weights by women and young persons. Operations such as "shuttle kissing" and artificial humidification were to be dealt with, night baking was to be abolished except in special cases, in agreement with the International Convention. A weekly rest period of not less than 24 consecutive hours was to be accorded every protected person employed between 6 p.m. on Saturdays and 6 a.m. on Mondays. The working hours of protected women, young persons and children were to be brought down to 48 per week, no spell to be longer than 4½ hours. These improvements were in line with the Washington Convention to which we are parties. The provisions were also to apply to shipbuilding repairing and overhauling and the scaling and painting of boilers, holders and bilges. Unfortunately, the Labour Government was turned out before the later stages of the Bill could be taken. 292/840/1/15